Struktur Fisik Dan Batin Puisi Kimi Shinita Mou Koto Nakare Karya Yosano Akiko - Zaki Ainul Fadli; Luqyana Salsabila (Diponegoro University, 2020)
(Title: Physical and Inner Structure of the Poetry of Kimi Shinita Mou Koto Nakare by Yosano Akiko) This research examines Japanese poem shintaishi, Kimi Shinita Mou Koto Nakare by Yosano Akiko using structural and feminism approach. This research aims to understand the structurally context and the meaning of feminism contained in the poem. Yosano Akiko, whose real name is Shou Hou, is the first famous Japanese female poet in the late Meiji era. At that time when Japan was struck by war, the position of women in social and political life had shifted the view that physically women are not strong enough to contribute to the war that reduced the role of women. Women do not see war with an objective view but rather see it subjectively, which they associated with the author’s own condition. The results showed that in addition to convey her aspirations as a woman after the war, there were several images which are contained in Kimi Shinita Mou Koto Nakare.